Pekanbaru Mayoral Election 2024: Critical Discourse Analysis Review - Syed Agung Afandi; Rizki Erdayani; Muslim Afandi; Nail Hidaya Afandi (Jurnal Politikom Indonesiana, 2022)
This study was motivated by the widespread coverage of the nomination for Mayor of Pekanbaru in 2024 by Riau's local media. This study's objective is to examine the alignments of GoRiau.com in shaping the reputation of political actors in the Pekanbaru Mayoral election for the years 2024 to 2029. This study employs the Fairclough model's text analysis, discourse practice, and sociocultural practice approaches. This research's fundamental technique is tapping, with the method of analyzing social change models. According to the results of this study, GoRiau.com is aligned with Agung Nugroho. In addition to being among the names that dominate the number of reports, he also benefits from the media's political narrative. Agung Nugroho's news history is dominated by political issues, and the content produced has generally resulted in favorable public opinion. Several conditions affect the neutrality of the mass media, including the Democratic Party's two-period political dominance in Pekanbaru City, Agung Nugroho's success in obtaining the most votes in Pekanbaru City during the 2019 Riau Legislative Election, and Agung Nugroho's strategic position as Deputy Chair of the Riau Legislative Institution, in addition to being the chairman of the Riau Democratic Party. This mass media alignment will benefit Agung Nugroho in the upcoming 2024 Pekanbaru mayoral election, as one of the largest media outlets in Riau. Keywords: Election, Pekanbaru, Critical Discourse Analysis